A comparative evaluation of sealability of three different obturation techniques using rotary instrumentation for canal preparation - Kitty Sidhu; B K Raghavendera Rao; Soheyl Sheikh; Neha Bansal; Ritika Bahuguna (Wolters Kluwer Medknow Publications, 2015)
Introduction: A well-fitted root canal filling prevents percolation and microleakage of periapical exudate into the root canal space, prevents reinfection and creates a favorable biological environment for healing to take place. Several techniques using gutta-percha have been used in an attempt to achieve a void-free, homogeneous filling. Aim: Three different obturation techniques that are Thermafil obturation, cold lateral condensation and warm vertical condensation using rotary canal technique were compared. Materials and Methods: This study was in vitro study. Forty-five extracted permanent human premolars with single canal, and fully developed apices were selected for the study. Statistical Analysis: This was done with the help of analysis of variance. Results: There was leakage measuring 0.5-3.5 mm in 73.3% of roots in group I, 80% in group II and 40% in group III. Similarly, the leakage was 3.51-6.5 mm in 20% of the roots in group I, 13.3% in group II and group III. The leakage was found to be more than 6.5 mm in 6.7% of the roots in group I and II and 46.7% in group III. There was sealer extrusion in two teeth in group I and II and in four teeth in group III. Conclusions: It was observed that the warm vertical condensation and lateral condensation techniques were more effective in restricting apical dye penetration. However, the results of this in vitro study need to be confirmed by further in vivo research.